Penerapan Model Pembelajaran Cooperative Script dalam Meningkatkan Keterampilan Berbicara Siswa pada Mata Pelajaran Bahasa Indonesia - Salam, Rosdiah; Achmad, Widya Karmila Sari; Indriani, Risma (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The problem in this research is the low speaking skills of class IV students at SDN No.38 Parasangan Beru Kabupaten Takalar. The approach used in this research is a descriptive qualitative approach. This type of research is Classroom Action Research (PTK). The results of the research showed that there was an increase in students' classical speaking skills from cycle I to cycle II. Meanwhile, in student learning activities, achievements in cycle I were in the poor category, while in cycle II achievements were in the good category. The final test of speaking skills in cycle I was in the poor category, while in cycle II it was in the good category. From the results of this analysis, it can be concluded that using the Cooperative Script learning model can improve speaking skills in class IV students at SDN No.38 Parasangan Beru Kabupaten Takalar.